PEMETAAN SOCIO-ECONOMICS UMAT HINDU DI DESA MUTIHAN KECAMATAN GANTIWARNO KABUPATEN KLATEN - I Wayan Putu Sari; Dwiasa Sambhawa Dharma; I Wayan Tudy Subawa (Jawa Dwipa, 2026)
The economic conditions of Hindus in Klaten Regency are known to be generally poor, especially those living in remote rural areas. The main source of income for Hindus is usually farming, which is only enough to meet the basic needs of the family. This study aims to comprehensively map the socioeconomic conditions of Hindus in Mutihan Village. Specifically, this study seeks to determine the average household income and expenditure, identify the economic institutions that support the community, and explore the potential resources and expectations of the community regarding future economic empowerment programs. This study uses a mixed method approach that combines descriptive quantitative and qualitative methods. The findings show that the majority of Hindus in Mutihan Village are in the lower-middle income group. The livelihoods of the respondents vary greatly, ranging from pensioners, laborers, to village officials, but few of them work primarily in agriculture even though the area has agricultural potential. Demographically, the community's education level is dominated by elementary to high school graduates, with a limited number of college graduates. This mapping also identifies that some elderly residents are highly dependent on family support for their livelihood.